1991
DOI: 10.1099/0022-1317-72-11-2733
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic and intergenic recombination between temperature-sensitive mutants of vaccinia virus

Abstract: The frequency of recombination for a complete set of two-factor crosses between vaccinia virus mutations separated by distances of between 54 and 10 692 bp was determined. The results show that in intragenic crosses there is a linear relationship between the recombination frequency observed and distances between the mutations of up to 700 bp. However, no length dependence of the recombination frequency in intergenic crosses with a distance between mutations of 328 to greater than 10000 bp is observed. We attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Thus, while the mean length of a conversion track was 12 kbp, the median was only 2.6 kbp. The abundance of short conversion tracks would help favor intragenic recombination events, which can be detected between markers spaced only 54 bp apart (34). We should note that this estimate of the recombination frequency is lower than has been previously reported.…”
Section: Resultsmentioning
confidence: 65%
“…Thus, while the mean length of a conversion track was 12 kbp, the median was only 2.6 kbp. The abundance of short conversion tracks would help favor intragenic recombination events, which can be detected between markers spaced only 54 bp apart (34). We should note that this estimate of the recombination frequency is lower than has been previously reported.…”
Section: Resultsmentioning
confidence: 65%
“…In these cases, the distance error (blue and black horizontal error bars) was estimated from the size(s) of the restriction fragment(s) in which the mutation(s) resides (see Materials and Methods). Fathi et al reported actual standard deviations for each of the R f determinations (red-colored points with vertical error bars) (11). The error in R f is unknown for most of the individual crosses reported by Ensinger (7)(8)(9), but as a guide we show an estimated average absolute error of ϳ4% based upon what was reported for a subset of R f measurements (7).…”
mentioning
confidence: 69%
“…These data were culled from the published literature and updated (where possible) to include estimates of the marker positions on the VAC genome. These data represent many different crosses between temperature-sensitive markers and span distances up to about onethird of the VAC genome (8,9,11,16,28). Two features of these data are immediately obvious.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis of CPXV strain Germany 1998_2 showed that genome segments clustered with either the CPXV-like 1 or the CPXV-like 2 clade, whereas for the CPXV isolate HumLit08/1 similarities to both, the VARV-like and VACV-like clade, were observed. Recombination within OPV has, so far, been described in vivo [44,45] and in vitro [46,47,48,49], and might explain the observed mosaic genomes. However, a retrospective analysis of recombination is challenging when only limited numbers of sequences are available and the underlying phylogeny is not characterized in detail.…”
Section: Discussionmentioning
confidence: 99%